2018
DOI: 10.1097/mnm.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the histopathologic correlates of 18F-FDG PET heterogeneity in non-small-cell lung cancer

Abstract: Investigating the histopathologic correlates of 18 F-FDG PET heterogeneity in non-small-cell lung cancer. Nuclear Medicine Communications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…Previous studies have confirmed the correlation between histopathological heterogeneity and intratumoral heterogeneity in FDG distribution or FDG-PET-derived indices [12][13][14]. The coefficient of variation (COV) is a simple and reliable index that has been used in some recent articles [15].…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have confirmed the correlation between histopathological heterogeneity and intratumoral heterogeneity in FDG distribution or FDG-PET-derived indices [12][13][14]. The coefficient of variation (COV) is a simple and reliable index that has been used in some recent articles [15].…”
Section: Introductionmentioning
confidence: 89%
“…In non-small cell lung carcinoma [160], 3D-fractal dimension extracted from 18 FDG-PET/CT images was found to be an independent prognostic factor of disease-free survival, and combining glucose metabolism using SUV with morphological complexity described by fractal dimension improved diagnostic accuracy [161]. Importantly, 18 FDG-PET features, including texture heterogeneity metrics, were found to be associated with histopathological features computed on H&E images, providing a link between radiomic and phenotypic ITH [162].…”
Section: Radiomic Heterogeneitymentioning
confidence: 96%
“…Measures, such as image intensity, contrast, and texture, allow for clear delineation of internal structures, 99m Tc, 111 In and 123 I) and PET (e.g., 11 C and 18 F)], which can be integrated into any organic metabolite. 18 F is used to label glucose analog, 18 [153][154][155][156][157][158][159][160][161][162] a Abbreviations: CA, contrast agents; CNR, contrast-to-noise ratio; CT, computer tomography; DCE, dynamic contrast enhanced; DW, diffusion weighted; MRI, magnetic resonance imaging; PET, positron emission tomography; SNR, signal-to-noise ratio; SPECT, single photon emission computer tomography.…”
Section: Measuring Spatial Molecular and Microenvironmental Heterogen...mentioning
confidence: 99%
“…Attempts have been made to correlate the underlying histological and biological features of NSCLC with radiomic features from FDG PET imaging. Correlations have been observed between histopathological mean cell density and lacunarity (large gaps between clusters of cells) and standard FDG parameters, including SUVmean and total lesion glycolysis, first-order statistical features, including kurtosis and skewness, and FDG lacunarity [42]. Another study has shown associations between a number of texture parameters and NSCLC clinical stage and Ki67 IHC analysis of proliferation using k-nearest neighbours and support vector machine (SVM) methods [43].…”
Section: Nsclc: Defining Molecular Mechanisms From Imagingmentioning
confidence: 96%